Pentingnya Pendidikan Toleransi Terhadap Perbedaan Agama di SDN 79 Kota Bengkulu - Triyani; Risqi Melani Saputri; Jumi Rostiana; Juwita Santri (GHAITSA : Islamic Education Journal, 2025)
This study focuses on the importance of teaching tolerance in Indonesia, where cultural and religious diversity is both a strength and a challenge. Early childhood education is essential to shape students' character so that they can appreciate differences and live peacefully in a pluralistic society. At SDN 79 Bengkulu City, tolerance is demonstrated through students' participation in religious activities. This study aims to explain the role of tolerance education in addressing religious differences in schools. The method used is qualitative, with data collection through interviews, observations, and document studies. The main sources of information were the principal, religious teachers, and students in grades 5 and 6. Additional data came from school documents, interview photos, and observation notes. Observations helped understand tolerance practices, while interviews explored teachers' and students' views on tolerance education. Documentation provided further insight from school records. The findings showed: (1) most students had a good understanding of respecting religious differences, (2) some teachers used inclusive teaching methods, and (3) challenges included limited teacher training in integrating tolerance into lessons and inadequate classroom resources. This highlights the need for better teacher preparation and improved facilities to effectively support tolerance education.